Mediation As a Non- Litigation Effort in Settlement Dispute Land in Indonesia - Nurwidiatmo (KRTHA BHAYANGKARA, 2025)
Land is something the needs required by each Indonesian citizens. Land is the basic capital development. in life socialize in general hang his life on the benefit land and have relationship that is eternal with the state and the people. Therefore That law agrarianism in Indonesia in general general has arranged in Constitution Number 5 of 1960 concerning Basic Rules of Procedure Agrarian Law (UUPA), which is implementation (formel gesetz) Article 33 paragraph 3 of the 1945 Constitution which states that " Earth and water and wealth nature contained inside it controlled by the state and used as much as possible For prosperity of the people”. As action carry on from the related Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia with earth or land. then be taken out Constitution Number 5 of 1960 concerning Basic Rules Agrarian (hereinafter abbreviated as UUPA). Scientific articles This Use study law normative or study law literature that is research conducted with method research material library or secondary data. and types research on writing This is study juridical normative. namely reviewed with approach legislation It means something problem will seen from aspect the law with examine regulation legislation. Research results show that the law in Indonesia is still need to be completed For form arrangement about Mediation As a Non- Litigation Effort in Settlement Dispute Land in Indonesia